Calibration of Soil Phosphorus Test for Upland Rice Grown on Typic Kandiudox, Way Pangubuan, Lampung - Mas Teddy Sutriadi; Diah Setyorini; Dedi Nursyamsi (UNIVERSITY OF LAMPUNG, 2018)
Calibration of soil P test was conducted for Typic Kandiudox derived from Way Pangubuan, Lampung. A field experiment was carried out in dry and wet seasons. The dry season experiment in 2013 was designed by applying various soil P status: 0 X (very low), ¼ X (low), ½ X (medium), ¾ X (high), dan X (very high), in which X was the amount of P required to obtain P concentration of 0.2 mg P L-1 in soil solution. The wet season experiment was conducted in 2013/2014 with the P treatments of P fertilizer at 0, 8, 16, 33, dan 66 kg P ha-1 in the form of SP-36 with 3 replicates. The results showed that Colwell, Morgan-Wolf, and Olsen extraction methods were not suitable to determine P requirement for upland rice grown on Typic Kandiudox. Extraction methods of Bray-1, Truog, Mehlich, HCl 25%, dan Bray-2 were appropriate to estimate P fertilizer requirement for upland rice. Among all of these extractions, Bray-1 and Truog were the most appropriate. The level of soil P availability extracted using Bray-1 were classified into low (< 12.0 ppm P2O5), medium (12.0-26.0 ppm P2O5), and high status (> 26.0 ppm P2O5), whereas soil P availability status extracted using Truog consisted of low (< 9.0 ppm P2O5), medium (9.0-15.5 ppm P2O5), and high (> 15.5 ppm P2O5). Phosphorus fertilizer recommendation for upland rice grown on Typic Kandiudox with low, medium, and high soil P availability status were 33, 8, and 0-4 kg P ha-1, respectively, which equal to 200, 50, and 0-25 kg SP-36 ha-1, respectively.